DISTRIBUTIONS AND HISTORICAL RECORDS OF ALIPHATIC CARBOXYLIC ACIDS IN THE H15 ICE CORE FROM ANTARCTICA - ニシキオリ, ムツミ; カワムラ, キミタカ; フジイ, ヨシユキ; NISHIKIORI, Mutsumi; KAWAMURA, Kimitaka; FUJII, Yoshiyuki (National Institute of Polar Research, 1997)
P(論文) An ice core collected from Antarctica (site H15) has been studied for molecular distributions of fatty acids and dicarboxylic acids using capillary gas chromatography and mass spectrometry. Molecular distributions of normal saturated fatty acids (C_8-C_<30>) showed an even carbon number predominance with a maximum at C_<16> or C_<18>, suggesting that they were mainly derived from marine phytoplankton. The ice core fatty acids have been emitted to the atmosphere from the sea surface microlayers in the Southern Ocean through a bubble bursting process and subsequently transported long distances over the Antarctic ice sheet. Their concentrations fluctuated in the ice core with a range of 1-4110ng/kg-ice, showing lower values between the 1630s and 1840s and higher values after the 1850s. The lower concentrations may suggest depressed emission of marine-derived fatty acids to the atmosphere due to enhanced sea ice coverage whereas the higher concentrations after the 1850s may be caused from enhanced emissions from the ocean due to the retreat of sea ice. The former is probably associated with the Little Ice Age, the latter with global warming. Unsaturated fatty acids (C_<16 : 1>, C_<18 : 1> and C_<18 : 2>) were also detected in the ice core together with their unique photochemical oxidation product : C_9 α, ω-dicarboxylic acid (azelaic acid). Interestingly, concentration ratios of azelaic acid to unsaturated fatty acids in the ice core showed a rapid increase after the 1970s, suggesting that photochemical transformation of organic aerosols in the Antarctic atmosphere and/or in the surface of the ice sheet was enhanced after the 1970s. An enhanced oxidizing capability suggested in the Antarctic troposphere may be involved with ozone depletion in the stratosphere, which has been observed over Antarctica for the last two decades. departmental bulletin paper